Вплив кратності обробки молочної емульсії в пульсаційному гомогенізаторі - Дейниченко, Г. В.; Самойчук, К. О.; Левченко, Л. В.; Deinychenko, G.; Samoichuk, K.; Levchenko, L. (My University, 2016)
UK: Знайдено рівняння для визначення кратності обробки емульсії залежно від параметрів пульсаційного гомогенізатора: подачі емульсії в апарат, діаметра поршня (робочої камери), частоти й амплітуди коливання поршня. Показано зв’язок між ступенем гомогенізації та кратністю обробки. Обґрунтовано існування оптимального значення подачі емульсії в пульсаційний апарат, за якого якість обробки оптимальна, а енерговитрати мінімальні. RU: Найдено уравнение для определения кратности обработки эмульсии в зависимости от параметров пульсационного гомогенизатора: подачи эмульсии в аппарат, диаметра поршня (рабочей камеры), частоты и амплитуды колебаний поршня. Показана связь между степенью гомогенизации и кратностью обработки. Обосновано существование оптимального значения подачи эмульсии в пульсационный аппарат, при котором качество обработки оптимальное, а энергозатраты минимальные. EN: The article is a part of the cycle of articles, devoted to the efficiency increase of the pulsation homogenizer of milk emulsion. Dispersion of milk fat in the pulsation homogenizer is caused by impulsive shake action while the piston with openings vibrates. Prospective use of the impulsive homogenizer lies in the possibility to create high-rate flowing around fat globules of the surrounding plasma which is the principal reason for their destruction. One of the indefinite influence factors of the emulsion homogenization process in the pulsation machine is treatment multiplicity, thus the aim of the research is analytical research of this factor’s influence on qualitative and power indexes of milk homogenization. The influence of one of the key indexes of the pulsation homogenizer process – emulsions supply has been discovered. Specific energy consumption of the process decreases with the supply increase. Moreover, at once the amount of passageways of milk emulsion through the piston openings decreases – treatment multiplicity, which reduces milk homogenization degree. The equation is found based on classic kinematic and hydrodynamic dependences to determine emulsion treatment multiplicity depending on the designkinematic parameters of the pulsation homogenizer: emulsion supply to the machine, diameter of piston (process chamber), frequency and amplitude of piston oscillation. The analysis of this equation shows that to increase the homogenization degree (increase of treatment multiplicity) it is necessary to decrease emulsion supply to the machine and increase the piston diameter (process chamber), frequency and amplitude of piston oscillation. The connection between homogenization degree and treatment multiplicity is shown. Based on the experimental data of the influence of milk treatment multiplicity in valve homogenizers, the assumption is made that for the pulsation machine there is such an optimal value of productivity, higher than the homogenization efficiency, which does not meet quality requirements. At the same time decrease of supply (at unchanging amplitude and frequency of vibrations and diameter of piston) is inefficient because of the increase rates of specific energy consumption are higher than increase rates of homogenization efficiency. The derived dependences supplement analytical model of fat emulsions homogenization in the pulsation homogenizer, and allow decrease substantially the volume of experimental researches of pulsation homogenization of milk.
Влияние кратности обработки молочной эмульсии в пульсационном гомогенизаторе
Influence of multiplicity of milk emulsion treatment in pulsation homogenizer
Keywords: гомогенізація; емульсія; молоко; гомогенізатор; диспергування; теорія; гомогенизация; эмульсия; гомогенизатор; диспергирование; теория; homogenization; pulsation homogenizer; energy consumption; theory